Flow Immersive: A Multiuser, Multidimensional, Multiplatform Interactive Covid-19 Data Visualization Tool - DiBenigno, Michael; Kosa, Mehmet; Johnson-Glenberg, Mina C. (Frontiers in Psychology, 2021)
Covid-19 has prompted a surge of data visualizations that have been published for public consumption, yet, many have not had broad appeal or may have not been well-understood by laypeople. A data storytelling platform called Flow Immersive has been created to successfully engage both laypeople and experts in understanding complex information. This tool integrates emerging technologies [e.g., augmented reality (AR) and virtual reality (VR)] with a multiplatform, multiuser publishing approach. From October 2020 to December 2020, Flow’s Covid-19 AR videos captured 9 million (9,000,000) views, and have been used in multiple professional presentations. This paper documents the journey from development to deployment, and some user feedback which all led to breakthroughs in scalability and higher levels of engagement.